Electrospun aligned poly(ε-caprolactone) nanofiber yarns guiding 3D organization of tendon stem/progenitor cells in tenogenic differentiation and tendon repair - Yang, Qiao; Li, Jianfeng; Su, Weiwei; Yu, Liu; Li, Ting; Wang, Yongdi; Zhang, Kairui; Wu, Yaobin; Wang, Ling (Frontiers in Bioengineering and Biotechnology, 2022)
Hierarchical anisotropy structure directing 3D cellular orientation plays a crucial role in designing tendon tissue engineering scaffolds. Despite recent development of fabrication technologies for controlling cellular organization and design of scaffolds that mimic the anisotropic structure of native tendon tissue, improvement of tenogenic differentiation remains challenging. Herein, we present 3D aligned poly (ε-caprolactone) nanofiber yarns (NFYs) of varying diameter, fabricated using a dry-wet electrospinning approach, that integrate with nano- and micro-scale structure to mimic the hierarchical structure of collagen fascicles and fibers in native tendon tissue. These aligned NFYs exhibited good in vitro biocompatibility, and their ability to induce 3D cellular alignment and elongation of tendon stem/progenitor cells was demonstrated. Significantly, the aligned NFYs with a diameter of 50 μm were able to promote the tenogenic differentiation of tendon stem/progenitor cells due to the integration of aligned nanofibrous structure and suitable yarn diameter. Rat tendon repair results further showed that bundled NFYs encouraged tendon repair in vivo by inducing neo-collagen organization and orientation. These data suggest that electrospun bundled NFYs formed by aligned nanofibers can mimic the aligned hierarchical structure of native tendon tissue, highlighting their potential as a biomimetic multi-scale scaffold for tendon tissue regeneration.